Histone mRNA degradation in vivo: the first detectable step occurs at or near the 3' terminus. - Ross, J (1986)
The first detectable step in the degradation of human H4 histone mRNA occurs at the 3' terminus in a cell-free mRNA decay system (J. Ross and G. Kobs, J. Mol. Biol. 188:579-593, 1986). Most or all of the remainder of the mRNA is then degraded in a 3'-to-5' direction. The experiments described here were designed to determine whether a similar degradation pathway is followed in whole cells. Two sets of short-lived histone mRNA decay products were detected in logarithmically growing erythroleukemia (K562) cells. These products, designated the -5 and -12 RNAs, were generated by the loss of approximately 4 to 6 and 11 to 13 nucleotides, respectively, from the 3' terminus of histone mRNA. The same decay products were observed after a brief incubation in vitro. They were in low abundance or absent from cells that were not degrading histone mRNA. In contrast, they were readily detectable in cells that degraded the mRNA at an accelerated rate, i.e., in cells cultured with a DNA synthesis inhibitor, either cytosine arabinoside or hydroxyurea. During the initial stages of the decay process, as the 3' terminus of the mRNA was being degraded, the 5'-terminal region remained intact. These results indicate that the first detectable step in human H4 histone mRNA decay occurs at the 3' terminus and that degradation proceeds 3' to 5', both in cells and in cell-free reactions.